ARTEMISININ PRODUCTION BY SHOOT CULTURE OF ARTEMISIA CINA BERG. EX POLJAKOV - Maria Marina; Aziz Purwantoro; C. J. Soegihardjo (Indonesian Journal of Pharmacy, 2003)
Artemisinin is a secondary metabolite has a potential effect as an antimalaria. Research in artemisinin content in A. cina from shoot culture have not been reported. The aim of this research were:(i) to know the ability of A. cina shoot culture to produce artemisinin, (ii) to asses the effect of concentration of yeast extract, sucrose and their combination in promoting the production of artemisinin, (iii) to determine the highest artemisinin concentration produced by shoot culture in the medium containing different concentration of yeast extract, sucrose and their combination. The factorial of randomised complex block design (RCBD) was used in this experimental design. The first factor was concentration of sucrose ( 1%, 3%, 5%, 7%) and the second factor was concentration of yeast extract (0 mg/l, 100 mg/l, 200 mg/l, 300 mg/l). HPLC was used. To analyse quantitatively the artemisinin production, analysis of variance (ANOVA) and DMRT were used to analyse the data. The results showed that the addition of yeast extract and sucrose increased the concentration of artemisinin from the A. cina shoot culture. The highest artemisinin content produced was 14.035 mg/g dry weights which was produced by combination of 3 % sucrose concentration and 200 mg/l yeast extract. This result suggest that A. cina shoot culture could be used as a method to producing artemisinin.Key words : Artemisinin, shoot culture, Artemia cina Berg. Ex Poljakov